Potential of insect frass as plant fertilizer and plant growth promoter on Mung bean (Vigna radiata) - Tan, Wan Joo (2016)
The increment of the usage of commercial fertilizers caused high production cost and damage of environment in agricultural sector nowadays. The research was done to test the fertilizing effect of frass in different forms and the effect of different dosages applied on the plant growth of Vigna radiata. The experiment was carried out using frass in both suspension and solid form with ﬁve different dosages. Chlorophyll content, stem diameter, plant height and plant weight were recorded as plant growth parameters to test the effect of frass towards the plant performance. The result showed that there was no signiﬁcant difference (p >0.05) between the effect of the solid insect frass and suspension form of frass. In contrast, the dosages applied to the plants gives signiﬁcant effect on the plant growth however there are no signiﬁcant difference between the treatments. The frass of Blaptica dubia showed positive potential as plant fertilizer.